University Students’ Perceptions of Social Media as a Learning Tool: A Science Discipline Perspective - Hashim, K.; Kutbi, I.; Al-Sharqi, L. (Advances in Social Sciences Research Journal, 2017)
Social media can have a considerable impact on students’ learning. Studies indicate promising use of social media in improving learning environments. This study investigates King Abdulaziz University (KAU) science discipline (including engineering and computer science) students’ perceptions of social media as a learning tool. Data were compiled through a specially designed survey. The sample size was 1461 students of different ages and genders representing KAU science discipline colleges. The results indicate that a moderate majority of KAU science discipline students are using social media tools in their learning at university and have the preference to integrate social media as a tool in their learning. The paper also documents gender significant differences on preferred social media tools, purposes of social media usage and dominant issues relating to use of social media in learning. The findings reinforce the notion that adoption of social media as a learning tool is advantageous and do not reveal any obvious disadvantages. Such findings can encourage academic planners and instructors to endorse and implement social media tools in the learning context of students within the science discipline.